2023
DOI: 10.1007/s10658-023-02701-3
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of clubroot disease: how successful are endophytic fungi and bacteria?

Abstract: The commercial aspect of growing Brassica crops has always been influenced by the worldwide occurrence of the clubroot pathogen, Plasmodiophora brassicae. Clubroot symptoms reduce crop yield dramatically and the resilient protist is hard to eradicate from infested soils. Chemical treatments are not so efficient and their use is allowed only in a few areas of the world, none of them in the EU. The majority of clubroot control is mediated by using resistant crops, but not all species have good or durable resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Although the amount of research on biocontrol of P. brassicae –cruciferous is not as vast as in other soil-borne pathosystems, the increasing scientific literature on this area shows the interest and the potential of this method against clubroot ( Auer and Ludwig-Müller, 2023 ). Since some fungicides with demonstrated efficacy to control clubroot are banned in the European Union, and there is interest in developing sustainable clubroot management around the world, further work based on the combination of crop management practices, resistant cultivars, and biological control approaches must be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the amount of research on biocontrol of P. brassicae –cruciferous is not as vast as in other soil-borne pathosystems, the increasing scientific literature on this area shows the interest and the potential of this method against clubroot ( Auer and Ludwig-Müller, 2023 ). Since some fungicides with demonstrated efficacy to control clubroot are banned in the European Union, and there is interest in developing sustainable clubroot management around the world, further work based on the combination of crop management practices, resistant cultivars, and biological control approaches must be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…A low number of Trichoderma species have been tested against P. brassicae , and in some works, the species were not reported. From the review by Auer and Ludwig-Müller (2023) , just a few species have been tested, mainly T. harzianum followed by T. virens , T. asperellum , and T. koningiopsis . Moreover, no studies on modes of action by the biocontrol agents against P. brassicae were done, with the exception of that described in Yu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A trend can be observed in the isotianil treatments, particularly for experimental year 2. Auer and Ludwig-Müller [35] reviewed the control efficacies of various biocontrol agents against clubroot and found that the majority of studies reported a reduction in clubroot symptoms following treatments with biological control agents (BCA). Interestingly, some studies reported efficacies with more severe symptoms observed after BCA treatment.…”
Section: Infection-related Changes In Response To Host Plantsmentioning
confidence: 99%